2016
DOI: 10.1097/aln.0000000000001336
|View full text |Cite
|
Sign up to set email alerts
|

AMPAkines Target the Nucleus Accumbens to Relieve Postoperative Pain

Abstract: Background AMPAkines augment the function of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the brain to increase excitatory outputs. These drugs are known to relieve persistent pain. However, their role in acute pain is unknown. Furthermore, a specific molecular and anatomic target for these novel analgesics remains elusive. Methods The authors studied the analgesic role of an AMPAkine, CX546, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 99 publications
(155 reference statements)
2
23
0
Order By: Relevance
“…High-impact AMPAkines such as CX546 are more potent, but they have a narrower therapeutic window. In our current study, we did not observe any behavioral side effects or evidence of hyperexcitability with a systemic dose of 10mg/kg, and previous studies using this and similar doses have also shown the safety of this dose in rats [12, 13, 19, 20]. Nevertheless, in the future, it will be important to study the analgesic properties of newer low-impact AMPAkines which are more clinically applicable.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…High-impact AMPAkines such as CX546 are more potent, but they have a narrower therapeutic window. In our current study, we did not observe any behavioral side effects or evidence of hyperexcitability with a systemic dose of 10mg/kg, and previous studies using this and similar doses have also shown the safety of this dose in rats [12, 13, 19, 20]. Nevertheless, in the future, it will be important to study the analgesic properties of newer low-impact AMPAkines which are more clinically applicable.…”
supporting
confidence: 50%
“…AMPAkines are known to improve memory and cognition [6] and have been studied in a variety of neuropsychiatric diseases [11]. Two recent studies have shown that AMPAkines can relieve acute and chronic pain in several animal models, and the sites of action for these receptors are likely in the brain [12, 13]. Interestingly, AMPAkines are also known to increase the respiratory drive to antagonize hypoventilation in the context of opioids [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this circuitry, dopamine midbrain neurons, especially those connecting the VTA to the NAc and the NAc shell to the striatum (striato-nigro-striatal pathway) are considered the key elements ( Elman and Borsook, 2016 ). Not surprisingly, dysfunction of the VTA-NAc mesolimbic pathway has been associated with depression ( Russo and Nestler, 2013 ; Su et al, 2016 ) and neuropathic pain ( Ozaki et al, 2002 ; Taylor et al, 2015 ). Remarkably, previous studies have evidenced a dual behavior of those dopaminergic neurons, since a phasic burst occurs in response to an unexpected reward while a phasic firing inhibition occurs when an expected reward is not received ( Fields et al, 2007 ; Schultz, 2007 ).…”
Section: An Overview Of the Reward System Elementsmentioning
confidence: 99%